(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
This article considers the innovative development of the enterprise as a basis for improving the efficiency of its activities and at the same time as a process of high-quality change based on innovation. Theoretical and methodological aspects of the digital economy as an economy based entirely on digital computer technology and information and communication technologies have been studied. The necessity of involving enterprises in the system of strategic management of innovative development to create competitive advantages, such as market expansion, cost optimization, access to foreign markets, revenue growth has been proved.